Implementasi Program Tahfizh Al-Qur’an di Sekolah Menengah Kejuruan Swasta Kesehatan Haji Medan - Rifai, Ahmad; Wijaya, Candra; Anas, Nirwana (Kamaya: Jurnal Ilmu Agama, 2025)
The implementation of the Qur’an memorization program does not always run smoothly. Various challenges and obstacles often arise, both from the students, teachers, and the environment. For example, varying levels of student motivation, busyness with other academic activities, and lack of support from parents can affect the success of this program. The main objective of this study is to  analyze the implementation of the Al-Qur’an memorization program at the Haji Health Private Vocational High School in Medan. This type of research uses a qualitative approach in examining the research problem. This study empha sizes more descriptive data/information, in the formof data in the formof subject descriptions, descriptions of words or sentences, rather than limited data in numbers. The findings of this study are the planning of the Al-Qur’an memorization program and in order to achieve this program, all school residents carry out what has been planned at the beginning of the semester or the beginning of the year. Both the memorization teachers and students carry out according to the predetermined program. In the implementation of the Al-Qur’an memorization program, there are several programs that will be implemented including memorization activities, depositing, muraja’ah and Al-Qur’an memorization exams. The schedule for implementing the Al-Qur’an memorization program at the Medan Haji Health Private Vocational High School is as follows: Al-Qur’an memorization activities, Al-Qur’an memorization deposit activities, muraja’ah activities. Supporting and in hibiting factors in the Al-Qur’an memorization program atthe Medan Haji Health Private Vocational High School. Supporting factors include: good physical and psychological condition, full support from the foundation, teacher attention, certificates or rewards, motivation, and age. In hibiting factors include: not mastering the makharijul huruf and the science of tajwid, not repeating memorization, limited time allocation for teaching and learning activities  tomemorize the Al-Qur’an.